Modeling of gaseous emissions and soot in 3D-CFD in-cylinder simulations of spark-ignition engines: A methodology to correlate numerical results and experimental data. (May 2023) - Berni, Fabio; Mortellaro, Fabio; Pessina, Valentina; Paltrinieri, Stefano; Pulvirenti, Francesco; Rossi, Vincenzo; Borghi, Massimo; Fontanesi, Stefano
In order to reduce development costs and time-to market, 1D and 3D CFD tools can support engine design providing reliable estimations of the tailpipe emissions. In particular, 3D-CFD in-cylinder simulations can evaluate formation of both soot and gaseous pollutants inside the combustion chamber. The main issue in such kind of simulations is the validation against experimental findings. In fact, the complexity of the emission measurements does not allow a straightforward one-to-one comparison between numerical and experimental results. Therefore the present paper aims at providing, on the one hand, a robust numerical framework for both gaseous and solid emissions, on the other hand a dedicated post-processing for a fair comparison between simulations and experiments. From a numerical standpoint, a simplified approach is dedicated to gaseous emissions, while a more detailed one is reserved to soot modeling. The latter is based on the Sectional Method, whose reaction rates are tabulated following 0D chemical kinetic simulations of a purposely designed surrogate in a constant pressure reactor. Simulations and experiments proposed in the present analysis are referred to a high-performance turbocharged direct-injection spark-ignition engine operated at part-load and low rpms. On equal performance, revving speed and mean mixture quality, different injection timings are investigated. The developed numerical approach and post-processing ensure a good agreement between simulations and experiments.